FAKTOR-FAKTOR YANG MEMPENGARUHI BRAND LOYALTY KONSUMEN RESTORAN OPPA GALBY (CABANG : TANJUNG DUREN) - Tommy Ruslim (MANAJEMEN DEWANTARA, 2022)
The food industry is growing so rapidly that many new concepts are present to give a different feel. One of them is a restaurant with a buffet concept. While maintaining existing consumers is critical to competing today, this study focuses on factors influencing brand loyalty. OPPA GALBI is a Korean restaurant with a buffet concept. A sample in this study of 300 respondents at OPPA GALBI restaurants in Tanjung Duren. This study obtained that service quality, brand image, perceived quality, brand awareness, brand association positively influence brand loyalty.